Xi Jinping's China : the personal and the political - Stenslie, Stig; Galtung, Marte Kjær, 1976- (Boulder ; Colorado : Lynne Rienner Publishers, Inc., 2023)
"Using the rise of Xi Jinping as a lens, examines China's political development over the past decade"--
Leadership and politics in China -- Xi's climb through the ranks -- Concentrating power -- Extolling the leader -- An ideological Renaissance -- Stepping onto the world stage -- Is Xi a new Mao? -- Appendix 1. Timeline of the People's Republic of China -- Appendix 2. Timeline of Xi Jinping's life and career.
Includes bibliographical references and index.
Keywords: Xi, Jinping; China -- Politics and government -- 2002-